ANALYSIS OF DEFENSE STRATEGY POLICIES IN DEALING WITH THE POTENTIAL NEGATIVE IMPACTS OF THE SOUTH CHINA SEA CONFLICT - Angkasa Dipua; Lukman Yudho Prakoso; Dikry Rizanny Nurdiansyah (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
Several countries have implemented the diplomacy model using second-track diplomacy in solving various problems. With the dynamics of global, regional, and national strategic environmental conditions, the second track diplomacy model is a step that is considered to be effective and efficient in finding solutions to every problem between countries. The Indonesian Navy, which, according to Kent Booth, has one of its functions in carrying out diplomacy, has carried out several diplomatic steps. As an archipelago that has land and sea borders with ten neighboring countries, prioritizing this second track diplomacy model is necessary. The purpose of this study is to find a marine defense strategy in dealing with the potential impacts of the conflict that occurred in the South China Sea. Considering the vast territory of Indonesia's territorial sea, a method of sea defense strategies can apply this diplomacy model. This study uses a literature study by gathering various information from various sources, then the theory used in conducting discussions and analysis with the theory of Barry Buzan. This study concludes an input and recommendations for policymakers to prioritize second-track diplomacy in solving various existing problems, especially in Indonesia's sea border region with neighboring countries.